2008
DOI: 10.1182/blood-2007-11-125203
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate promotes lymphangiogenesis by stimulating S1P1/Gi/PLC/Ca2+ signaling pathways

Abstract: The lymphatic system plays pivotal roles in mediating tissue fluid homeostasis and immunity, and excessive lymphatic vessel formation is implicated in many pathological conditions, which include inflammation and tumor metastasis. However, the molecular mechanisms that regulate lymphatic vessel formation remain poorly characterized. Sphingosine-1-phosphate (S1P) is a potent bioactive lipid that is implicated in a variety of biologic processes such as inflammatory responses and angiogenesis. Here, we first repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 48 publications
8
80
0
Order By: Relevance
“…Our results demonstrate that the 3D sprouting of LECs into the collagen hydrogel (Movie S1) is morphologically similar to in vivo vessel sprouting as recently depicted in the mouse retina (25). We used a combination of VEGF-A, bFGF and S1P to promote lymphatic sprout formation since these factors are involved in pathological tumor and lymph node lymphangiogenesis (26,27), were previously validated in vitro (28), and yielded a more pronounced sprout formation in our assay than the individual growth factors. An advantage of our 3D assay is the automated image acquisition and analysis, which resolves these bottlenecks of conventional high-throughput screens.…”
Section: Discussionmentioning
confidence: 91%
“…Our results demonstrate that the 3D sprouting of LECs into the collagen hydrogel (Movie S1) is morphologically similar to in vivo vessel sprouting as recently depicted in the mouse retina (25). We used a combination of VEGF-A, bFGF and S1P to promote lymphatic sprout formation since these factors are involved in pathological tumor and lymph node lymphangiogenesis (26,27), were previously validated in vitro (28), and yielded a more pronounced sprout formation in our assay than the individual growth factors. An advantage of our 3D assay is the automated image acquisition and analysis, which resolves these bottlenecks of conventional high-throughput screens.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, Sphingosine-1-phosphate (S1P), a potent bioactive lipid that is implicated in a variety of biologic processes such as inXammatory responses and angiogenesis, was reported as a lymphangiogenic mediator (Yoon et al 2008). S1P induces the migration and capillary-like tube formation of lymphatic endothelial cells in vitro and lymphangiogenesis in vivo.…”
Section: Other Regulators Of Lymphatic Vascular Developmentmentioning
confidence: 99%
“…S1P is a known chemoattractant for a variety of cell types [28,31,32,53,54]. Furthermore, activation of S1PR1 by S1P promotes lymphangiogenesis via Gai-dependent signalling [33]. However, the full recirculation of cell culture media in the IFC takes 5 min, whereas the HLMVECs migrate on the timescale of multiple hours.…”
Section: Cs-l15mentioning
confidence: 99%
“…It has been previously shown that S1P is required for lymphangiogenesis and EC motility [33]. We therefore hypothesized that S1P might itself play a necessary role in the inward migration triggered by impinging flow.…”
Section: S1pr1 Is Required For Persistent Directional Migration In Rmentioning
confidence: 99%
See 1 more Smart Citation